3-Dimensional Versus 2-Dimensional Comparison of Knee Valgus Collapse during Vertical Jump: Clinical Implications for ACL Risk of Injury Assessment - Cesar, Guilherme M; Pfeifer, Chase M; Burnfield, Judith M (Journal of Sports Medicine and Therapy, 2017)
Time-efficient screening of lower extremity biomechanics to identify potential injurious movement patterns is crucial within athletic medicine settings. When considering biomechanical risk factors for anterior cruciate ligament injuries, several screening tests have been used to assess dynamic knee valgus. Current methods involving 3-dimensional motion capture systems are considered gold standard for such assessment; however, these methods are time consuming and require expensive materials. This study investigated the use of 2-dimentional kinematic evaluation during a standardized vertical jump athletic assessment to screen for potential lower extremity risk of injury. 50 collegiate athletes, 25 male and 25 female, from various sports participated in the study. The vertical jump was chosen because it is a common performance evaluation test that is regularly performed several times a year, providing consistent opportunities for screening while not creating additional obligations for the student athletes. Results showed that the 2-dimentional evaluation method had strong correlations (P<0.0001) with the gold standard 3-dimensional evaluation, suggesting that an accelerated 2-dimentional screening process can be used as a first step to screen for potential injurious lower extremity movement patterns.